TINGKAT INFESTASI CACING SALURAN PENCERNAAN PADA SAPI BALI DI KECAMATAN SUKOHARJO KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Putri Handayani; Purnama Edy Santosa; Siswanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
Research on infestation rate of the digestive fluke on Bali cattle in the Sukoharjo Sub-district , Pringsewu District, Lampung Province held in December 2014 and January 2015. The purpose of this research was to determine the infestation rate of the digestive fluke in Sukoharjo sub-district, Pringsewu District, Lampung Province. The method used is a survey with proportional random sampling, the stool samples obtained 131 Bali cattle. Analysis of the data used in the study is descriptive. The parameters observed were gastrointestinal worm eggs that Paramphistomum sp., Haemonchus sp., Oesophagustomum sp., Mecistocirrus sp., Cooperia sp., Ascaris sp., Trichostrongylus sp., and Nematodirus sp .. The results of this study showed that the prevalence of Bali Cattle that infected Paramphistomum sp. is 74.05%, Haemonchus sp. is 4.58%, Oesophagustomum sp. is 18.32%, Mecistocirrus sp. is 2.29%, Cooperia sp. is 0.76%, Ascaris sp. is 0.76%, Trichostrongylus sp. is 1.53%, and Nematodirus sp. is 0.76%. (Keywords : Infestation rate, Bali cattle, gastrointestinal worm).